Reactive power control of grid-connected solar photovoltaic system (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Solar Photo Voltaic (SPV) based distributed generation is providing a clean and green energy to meet human needs nowadays. In grid-connected mode, most of the capacity of converter circuit is under-utilized as peak power is available for a small duration in the daytime and no utilization during the night. The converter used for PV system may be modified to work as STATCOM, that is capable to convert DC to AC and can compensate reactive power simultaneously. Thus in daytime this modified PV-STATCOM system supply both active and reactive power and in the night it will supply only reactive power resulting in better utilization of Power Conditioning System (PCS). In this paper, modified PV-STATCOM is tested in the grid-connected mode through simulation in MATLAB/Simulink/SimPower under various operating conditions. The proposed system supply active and reactive power locally in the grid-connected load resulting in less burden on the grid.